Pengembangan Aplikasi Pengolahan Pertanian Hortikultura Berbasis Web (Studi Kasus: Desa Wonosari Kecamatan Tutur) - Filan Maula Andini; Agi Putra Kharisma; Sutrisno Sutrisno (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Agriculture is one of these sectors which is very important in helping the Indonesian economy. In addition, primary human needs also come from agriculture. The agricultural sector is also very diverse, one of which is horticulture, where the harvest is directly used to meet daily needs ranging from fruit, vegetables, or nuts. In the process, can be sure that there are not a few farmers who have the same problems as what happened to farmers in Desa Wonosari Kecamatan Tutur. The problems that are often faced by farmers in the village include, starting from who have problem lack of fund, difficulty of managing accountancy, and often got a crop failure cause of unpredictable market prices. Apart from the previously mentioned, the selection of plant medicine very influential in accordance with weather conditions therefore it required experience and information. Therefore, this research offers solutions in the form of developing agricultural processing applications especially horticulture with web-based in order to help farmers in processing horticultural agriculture by accessing information, managing accountancy, accessing the latest prices of agricultural marketing, can simulate business analysis when going to start farming according to the budget and can question answering between farmers to share experiences or just share information. System developing by Object Oriented approach with M-V-C (Model-View-Controller) concept pattern from CodeIgniter framework. The method used is Waterfall model and the database in the form of MySQL. Then, at the testing phase done by implementing functional requirement testing equipped with strategy unit and integration testing with whitebox method also validation testing with blackbox method that produces 100% valid value. As for non-functional requirement testing is done by compatibility testing using SortSide tool in order to know the system can be run on different browsers.